Comparison of the hard and soft tissue changes of bimaxillary protrusion patients treated with Begg and MBT techniques: a cephalometric study - Sarkar, Nilanjana; C., Karunakara B.; Goel, Sumit; Reddy, Sumitra (International Journal of Scientific Reports, 2021)
Background: The effective treatment of bimaxillary protrusion needs a sound knowledge of the mechanics and expertise to control the tooth movement and the unwanted side effects. To obtain a desired finish there is a need to study and compare the mechanics used for correction of bimaxillary protrusion. The aim of this study was to quantify and compare the skeletal, dentoalveolar and soft tissue effects of Begg and MBT mechanotherapies in the treatment of bimaxillary protrusion cases. Methods: In the present study, cephalometric comparison of the two mechanotherapies, Begg and MBT appliances was done retrospectively. The subjects were selected on the basis of pretreatment characteristics. The sample consisted of 40 patients (20 in each group) with an age range of 12-24 years. Pre- and post-treatment cephalograms were taken and traced on 75μm lacquered polyester acetate tracing papers using a 0.05” lead pencil. Results: The present study showed that Begg and the MBT appliances were equally effective in treating bimaxillary protrusion with first premolar extraction to satisfactory end results. Treatment with both the appliances resulted in significant amount of upper and lower anterior retraction and achievement of a pleasing facial appearance and profile. Conclusions: Good torque control, if used in Begg mechanotherapy will result in achieving similar treatment outcome as obtained with MBT technique.